Conversational Implicature in Beauty and Beast Movie Directed by Bill Condon - Sayyid Khairunas; Juniato Sidauruk; Rizky Mirani Desi Pratama; Tesalonika Omega Mazmur Dwi Natalia (Wanastra: Jurnal Bahasa dan Sastra, 2020)
The objective of this research is to find out and analyze the types of conversational implicature and the maxim violation in Beauty and the Beast movie. Beauty and the Beast movie was directed by Bill Condon and released in 2017. The method used to conduct this research is descriptive qualitative method. To analyze the types of conversational implicature and the maxim of violation, the writers retrieved the theory from P.H.Grice. Grice states that there are two types of conversational implicature and there are four maxims in cooperative principles. The result of this research indicates that: (1) There are two types of conversational implicature occured in Beauty and the Beast movie; those are generalized conversational implicature and particularized conversational implicature.  The  most common  types  of  conversational  implicature that occur in Beauty and the Beast movie is generalized conversational implicature, (2) There are four maxim which violated in Beauty and the Beast movie; those are maxim of quality, quantity, relation and manner. The most violated maxim in Beauty and the Beast movie is maxim of quantity.